2020
DOI: 10.1002/cctc.202001645
|View full text |Cite
|
Sign up to set email alerts
|

CuO{001} as the Most Active Exposed Facet for Allylic Oxidation of Cyclohexene via a Greener Route

Abstract: Allylic oxidation of olefins to α,β‐unsaturated carbonyl compounds, especially2‐cyclohexen‐1‐one, by the oxidation of cyclohexene is a prime chemical transformation in the organic industry due to its immense application as an intermediate in the synthesis of fine chemicals, pharmaceutical products, and perfumery products. Herein, we demonstrate microstructured copper oxide (CuO) as an efficient catalyst to oxidize cyclohexene to 2‐cyclohexen‐1‐oneand other value‐added intermediates in the presence of aerobic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…allowed scientists to develop materials with different shapes (nanowires, nanocubes, nanoribbons, nanoflowers, nano-octahedra, nano-shuriken, nanofiber, etc. ), morphologies, and sizes [75,76]. The copper salts (chloride, nitrate, sulfate, or acetate) could be used as precursors to obtain the CuO nanostructures.…”
Section: General Considerations On the Most Important Metal Oxide Sem...mentioning
confidence: 99%
“…allowed scientists to develop materials with different shapes (nanowires, nanocubes, nanoribbons, nanoflowers, nano-octahedra, nano-shuriken, nanofiber, etc. ), morphologies, and sizes [75,76]. The copper salts (chloride, nitrate, sulfate, or acetate) could be used as precursors to obtain the CuO nanostructures.…”
Section: General Considerations On the Most Important Metal Oxide Sem...mentioning
confidence: 99%
“…The 3D CuO flowers exhibited the highest catalytic activity, which was ascribed to their high energy {001} exposed facets. 100 Dutta et al demonstrated that the partial oxidation of allyl ethers with Li was promoted by a mesoporous Mn 2 O 3 catalyst (Scheme 6). Here, N -hydroxyphthalimide and trichloroacetonitrile were used as promoting agents and the labile lattice oxygen present on the surface of mesoporous Mn 2 O 3 catalyst played a vital role in the catalytic activity.…”
Section: Transition Metal Oxide Catalysts For C–h Activationmentioning
confidence: 99%
“…Particularly, for selective allylic oxidation of cyclohexene, transition metal (e.g., Fe, Cr, Cu, V, etc.) organic framework catalysts 5,8 nitrogen-doped carbon nanotubes, 2 mesoporous etched halloysite nanotube supported Co 2+ , 1 and some copper based (microstructure copper oxide (CuO) 9 and magnetically recoverable copper oxide) 10 catalysts with molecular oxygen as an oxidant were previously reported.…”
Section: Introductionmentioning
confidence: 99%